Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan Kejadian Mual Muntah Pada Kehamilan Trimester Pertama Di Poskesdes Ampalu Kota Pariaman Bidan Helfiati, Amd. Keb. - Rika Armalini; Prasetyaningsih Prasetyaningsih (Jurnal Surya Medika (JSM), 2020)
Nausea, vomiting in pregnancy is physiological that occurs in the first trimester, which starts 6 weeks after the first day of the last menstrual period, and disappears 6-12 weeks later. The report shows that almost 50-90% of pregnant women experience it. Nausea, vomiting if not treated can cause severe dehydration until poisoning occurs. The purpose of this study was to link the knowledge and attitudes of pregnant women with the occurrence of nausea and vomiting in the first trimester of pregnancy in the Poskesdes Ampalu Midwife Helfiati, Amd. Keb. The study was conducted in July 2019. This type of research is analytic survey research with a cross-sectional design. The population in this study were all pregnant women who visited Helfiati Amd.Keb polindes as many as 40 pregnant women with a total sampling technique. Data were analyzed by univariate and bivariate by computerized statistical tests using SPSS Ver. 17 with a significance level α = 0.05 and a degree of confidence of 95%. The results of the univariate analysis showed that 52.5% of mothers experienced nausea, vomiting, 62.5% of low-knowledge mothers and 42.5% of mothers were negative about how to deal with nausea and vomiting. there is a significant relationship between knowledge (p = 0,000) and attitude (p = 0,000) with the incidence of nausea and vomiting in the first trimester of pregnancy in the Poskesdes Ampalu Midwife Helfiati, Amd.Keb 2019. The results of this study can be concluded that there is a significant relationship between knowledge and attitude with the occurrence of nausea, vomiting. With this research it is expected that health workers provide IEC services and improve health care counseling in an effort to increase the knowledge of pregnant women about how to cope with nausea, and also expect mothers to be more active in seeking information about physiological complaints during pregnancy, especially how to deal with nausea vomiting by following counseling activities held by health workers so that in the future more knowledge from mothers.